Hubungan Sedentary Lifestyle dengan Kejadian Obesitas pada Remaja Selama Masa Pandemi Covid-19 - Putu Awik Sirna Wardani; I Gede Putu Darma Suyasa; Idah Ayu Wulandari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
During the pandemic, teenagers are required to stay at home and limit their physical activity. Low levels of physical activity and the tendency to stay silent without doing physical activities, which is called a sedentary lifestyle.This study aims to determine the correlation between sedentary lifestyle and obesity among adolescents during Covid 19 pandemic. This study employed correlative analytic design with cross-sectional approach. The population of this study were 1467 students at SMA Negeri 4 Denpasar. There were 285 respondents recruited as sample of this study which were selected through proportional stratified random sampling. The data were collected by using questionnaire and analysed by using Spearman Rho test. From 285 respondents there were 39.6% of the respondents were male and 60.4% of respondents were female. 45.3% of the respondents were 16 years old. The finding showed that 9.8% of respondents experienced obesity and 3.5% of respondents experienced moderate obesity. In addition, the majority of respondents (37.5%) had a tendency to adopt a sedentary lifestyle, 43.5% of respondents had moderate physical activity and 18.9% of respondents had high activity. There was a correlation between correlation between sedentary lifestyle and obesity among adolescents during Covid 19 pandemic (p-value =0.05 r = -0.057). The students are expected to do physical activity at home during Covid 19 pandemic. Schools are advised to provide sports field for students and facilitate canteen staffs to attend training or seminars on nutrition, so that students could do optimal sports activities and their nutritional status is balance.